Public Expenditure on Agriculture and Economic Growth in Nigeria 1980-2024 - Okwajie, Fabian Ajijias (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
This study explored the connection between public spending in agriculture and economic growth in Nigeria from 1980 to 2024. The main objectives were to analyze the relationship between Total Public Expenditure in Agriculture, Recurrent Expenditure on Agriculture, Capital Expenditure on Agriculture, Public Debt Service on Agriculture (both Domestic and Foreign), and Real Gross Domestic Product (RGDP). Additionally, the study aimed to provide recommendations based on the findings to improve policy formulation and implementation for better public spending in agriculture and economic growth. Five research questions and four hypotheses guided the investigation. A qualitative method was employed, utilizing data from the National Bureau of Statistics, the Federal Ministry of Agriculture, and the World Bank. The findings indicated no significant relationship between Total Public Expenditure in Agriculture and RGDP, as well as no significant relationship between Recurrent Expenditure in Agriculture and RGDP. However, there was a significant relationship between Capital Expenditure in Agriculture and RGDP, as well as between Public Debt in Agriculture and RGDP. Key recommendations include prioritizing capital expenditures in agriculture to maximize their impact on economic growth, conducting a thorough evaluation of how these funds are allocated and utilized, streamlining operational costs, and focusing on value-added activities to enhance effectiveness. Additionally, a strategic approach to public debt is necessary, ensuring that borrowed funds are directed towards productive investments in agriculture that can yield long-term economic benefits